The International Graduate Summer School in Librarianship and Information Science, 1983 - Rashidan, H. (University of Malaya Library, 1983)
The International Graduate Summer School in Librarianship and Information Science, J 983, provided advanced courses for practising librarians throughout the world. The intensive two-month course successfully combined theoretical and practical instruction on various aspects of librarianship to suit the needs of the participants in the course. The methodology of instruction adopted by the competent tutors was lectures coupled with audio-visual demonstrations and visits to specific libraries to see the practical application of theories propounded in the lectures. The cosmopolitan composition of the participating librarians combined with the successful management and organisation, made the course very interesting, informative and useful.